2017
DOI: 10.1099/jmm.0.000485
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Actinomyces spp. in cervical exudates from women with cervical intraepithelial neoplasia or cervical cancer

Abstract: Patients with cervical cancer had a higher prevalence of the presence of Actinomyces compared to the CIN and control groups. This is the first study in which a deliberate search of this genus has been performed in women with cervical pathologies. The use of specific primers for each species facilitated their detection in comparison with traditional isolation methods. More information is necessary to understand the molecular mechanisms involved in the complex role that bacterial communities may play in the deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…As the bacterial density is high in mucous membranes, microbiota may also play a role in the development of pre-cancerous or cancerous lesions of the uterine cervix. 8 Although García et al 7 demonstrated a higher prevalence of actinomyces in patients with cervical pathology when compared with healthy women, the role of this pathogen in pre-invasive and invasive cervical lesions has not been yet confirmed.…”
Section: Dr Saez Perrottamentioning
confidence: 99%
“…As the bacterial density is high in mucous membranes, microbiota may also play a role in the development of pre-cancerous or cancerous lesions of the uterine cervix. 8 Although García et al 7 demonstrated a higher prevalence of actinomyces in patients with cervical pathology when compared with healthy women, the role of this pathogen in pre-invasive and invasive cervical lesions has not been yet confirmed.…”
Section: Dr Saez Perrottamentioning
confidence: 99%
“…The genera Fusobacterium , Actinomyces , and Parvinmonas were found to increase in advanced stage HPSCC. Genus Actinomyces is a dangerous bacterium that correlates with cervical carcinoma [ 32 ]. Genus Parvimonas ( Parvimonas micra) is connected with infection and gastric carcinoma [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other studies imply that these four genera are all oral opportunistic pathogens and can be linked to inflammatory reactions and cancer development [ 16 , 39 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 ]. Notably, a significant increase of Prevotella and Actinomyces has been previously reported in vaginal or cervical exudates from women with cervical dysplasia or cervical cancer [ 10 , 58 , 59 ]. This finding suggests the potential for the transfer of these opportunistic pathogens between the oral and vaginal tracts.…”
Section: Discussionmentioning
confidence: 99%
“…Actinomyces , which is significantly increased among smokers in our study, had been linked to higher gingivitis risk among cigarette smokers in other studies [ 67 , 68 , 69 , 70 , 71 ]. Cigarette smoking is an independent risk factor for cervical dysplasia occurrence and development [ 21 , 59 , 72 , 73 ]. We identified a significant positive relationship between the RLR pathway and Actinomyces among patients with dysplasia than the ones without, and among smokers than nonsmokers.…”
Section: Discussionmentioning
confidence: 99%